Services and Handling of Maternal Emergencies in Hospitals Based on Law - Naurah, Gladdays; Fatimah, Fitri; Simarmata, Marice; Sidi Jambak, Redyanto (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to research Services and Handling of Maternal Emergencies in Hospitals Based on Law.This research is qualitative research with a descriptive analytical approach. The data required in the research was collected through in-depth interviews with informants/subjects whose criteria had been selected using purposive sampling by the researcher. The conclusion of this material highlights the importance of understanding the legal basis that regulates maternal emergency services and management in hospitals, both from the perspective of the responsibilities of health institutions and the rights and protection of patients. With the Minister of Health Regulation Number 21 of 2021 concerning the implementation of health services during pre-pregnancy, pregnancy, childbirth and the post-natal period, contraceptive services and sexual health services. Article 16 paragraph (1) which reads